An Unusual Presentation of Merkel Cell Carcinoma in the Setting of Immunosuppression on TNF-Alpha Inhibitor Therapy - Kristen Delans; Rachel Semus; Nasiffa Hossain; Jack Ledford (Karger Publishers, 2022)
Merkel cell carcinoma (MCC) is a rare but deadly skin cancer, observed classically in the sun-damaged skin of older, white males. The cancer is characterized by rapid growth as well as high morbidity and mortality. In this article, we detail an atypical presentation of MCC in an African-American patient being treated with prednisone, methotrexate, and adalimumab for rheumatoid arthritis. Initially presenting as a subcutaneous nodule, the tumor in our patient was misdiagnosed first as an abscess and treated accordingly. Only after the subcutaneous mass failed to resolve with antibiotics as well as repeated incision and drainage was a biopsy performed, which yielded the final diagnosis. In the text, we detail the patient's symptomatology as well as steps that eventually lead to diagnostic confirmation. Our case demonstrates the importance of heightened clinical suspicion for MCC in immunosuppressed patients with unexplained subcutaneous nodules. Prompt diagnosis is crucial for positive outcomes; therefore, we aim to provide information that may aid in identification of MCC tumors in future patients. With the increasing use of biologic agents such as adalimumab to treat rheumatic disease, the literature is demonstrating an increasing incidence of previously "rare" malignancies such as MCC. It is crucial for physicians to convey these risks when initiating a patient on chronic immunosuppressive therapy and to provide routine surveillance for MCC and other complications.